2020
DOI: 10.1515/ntrev-2020-0096
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of functionalized carbon nanotubes for fluorescent biosensors

Abstract: Despite the development of pharmacy, there are still incurable diseases for which the medicine has not been found yet. Because many diseases are asymptomatic in their first stage of development, often early detection is the crucial factor in combating them. The article describes the process of synthesis of carbon nanotubes (CNTs) which can be useful in medical diagnostics. CNTs were synthesized by chemical vapor deposition. The obtained material was subjected to functionalization – attaching fluorescent marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…Figure 1 a shows the FT-IR spectra of SWCNTs and P-SWCNTs and it can be seen that peaks occurred near 1114, 1382, 1751, 2920, and 3436 cm −1 . For the SWCNTs, differences after atmospheric-pressure plasma treatment were observed as larger peaks at wavenumbers 1699 and 1385 cm −1 , which correspond to the carboxyl (–COOH) stretching vibrations of C=O and C–OH, respectively, while the peaks at 1110 and 2918 cm −1 correspond to the stretching vibrations of C–O and C–H, respectively [ 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 a shows the FT-IR spectra of SWCNTs and P-SWCNTs and it can be seen that peaks occurred near 1114, 1382, 1751, 2920, and 3436 cm −1 . For the SWCNTs, differences after atmospheric-pressure plasma treatment were observed as larger peaks at wavenumbers 1699 and 1385 cm −1 , which correspond to the carboxyl (–COOH) stretching vibrations of C=O and C–OH, respectively, while the peaks at 1110 and 2918 cm −1 correspond to the stretching vibrations of C–O and C–H, respectively [ 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Figure1ashows the FT-IR spectra of SWCNTs and P-SWCNTs and it can be seen that peaks occurred near 1114, 1382, 1751, 2920, and 3436 cm −1 . For the SWCNTs, differences after atmospheric-pressure plasma treatment were observed as larger peaks at wavenumbers 1699 and 1385 cm −1 , which correspond to the carboxyl (-COOH) stretching vibrations of C=O and C-OH, respectively, while the peaks at 1110 and 2918 cm −1 correspond to the stretching vibrations of C-O and C-H, respectively[42,43].The XPS spectra on the surface of SWCNTs and P-SWCNTs, as well as the atomic content concentrations of C and O, are shown in Figure1band TableS1(Supplementary Materials), respectively. It was found that the C 1s /O 1s ratios of the SWCNTs and P-SWCNTs samples were 0.04% and 0.09%, respectively.…”
mentioning
confidence: 99%
“…Multi-walled iron-filled carbon nanotubes were synthesized by catalytic chemical vapor deposition (CCVD) [19,27]. The synthesis process was carried out in a three-zone furnace, which allowed independent temperature control of each zone.…”
Section: Synthesis Of Fe-mwcntsmentioning
confidence: 99%
“…Surface modifications of carbon nanotubes can give nanotubes a number of applications in medical diagnostics, for example, attachment of a fluorescent dye to the surface of the nanotube and appropriate functionalization can contribute to the creation of biosensors that detect diseases and disorders at a very early stage. In combination with targeted therapy, it may provide the possibility of simultaneous monitoring of the effects of a given therapy [19].…”
Section: Introductionmentioning
confidence: 99%
“…without significantly altering their properties. [ 155 , 156 ]. Moreover, more active binding sites can be created on the surface of nanotubes making them more easily dispersible in various solvents.…”
Section: Carbon-based Nanomaterialsmentioning
confidence: 99%